PRACTICALITY TEST OF POWERPOINT LEARNING MEDIA. INTERACTIVE MATERIAL BUILD FLAT WITH CLASSIV SCIENTIFIC APPROACH PRIMARY SCHOOL - Olivia, Nesta; Darmansyah Bahar; Yanti Fitria (Study program PGSD FKIP Universitas Bung Hatta, 2023)
This research is motivated by the lack of teacher and student interaction in the mathematics learning process because the media used by the teacher is not attractive and not interactive so that students have difficulty understanding learning material. This study aims to produce interactive PowerPoint learning media based on a scientific approach to learning mathematics on flat shape materials for fourth grade elementary school students that are valid and practical. This type of research is research and development (Research and Development) with the research model used is the ADDIE type, namely analysis, design, development, implementation and evaluation. This research was conducted at the beginning of the odd semester. Research instruments include validity sheets and practicality sheets. In the validation process, the media is validated by one material expert and one media expert. In the practicality process, the media was tested by 1 teacher and 27 students. Based on the results of the research, the development of interactive PowerPoint learning media based on a scientific approach resulted in very valid criteria with an assessment percentage of 91.66% and very practical criteria with a percentage of 93.9%. Based on the research that has been done, it can be interpreted that interactive PowerPoint learning media based on a scientific approach is very valid and very practical to use as one of the learning media, especially flat shape material for fourth grade students.